Shelf-life and microbial community dynamics of super-chilled beef imported from Australia to China. (June 2019) - Chen, Xue; Zhang, Yimin; Yang, Xiaoyin; Hopkins, David L.; Zhu, Lixian; Dong, Pengcheng; Liang, Rongrong; Luo, Xin
Abstract: The aim of this study was to investigate the shelf-life and microbial community dynamics of super-chilled vacuum-packaged beef striploins imported from Australia to China after approximately five weeks of shipping time and an additional 15 weeks of storage at −1 °C ± 0.5 °C. Data analysis using a mixed model (REML) with time as the fixed effect and portion as a random effect, showed that the only beef quality trait that changed during storage was total volatile basic nitrogen (TVBN; P < .05), which reached the threshold of 15 mg/100 g between 15 and 20 weeks (including 5 weeks of transport). The total viable count (TVC) accounted for 78% of the variance in TVBN, when storage time was included in the model. Sensory scores decreased as storage time extended ( P < .05), but were still acceptable at 20 weeks. After 9 weeks, Carnobacterium spp. and Lactobacillus spp. dominated alternately and then Lactobacillus became the most prevalent bacteria. An operational taxominc unit based hierarchical cluster analysis using the unweighted pair-group method with arithmetic means was performed and it was shown that the bacterial communities tended to be consistent as storage time extended. Overall indications are that beef which is safe can be imported into China from Australia and aged for extended periods. Graphical abstract: Unlabelled Image Highlights: Shelf-life of beef cuts imported from Australia to China was evaluated based on TVBN. TVC accounted for 78% of the variance in TVBN during the storage of beef up to 20 weeks. The sensory scores decreased as time extended, but were still acceptable at 20 weeks. Carnobacterium spp. and Lactobacillus spp. dominated alternately after 9 weeks. Lactobacillus became the most prevalent bacteria in the end of the storage.